Different training approaches in karate - A review literature - Pal, S.; Yadav, J.; Katra, S.; Sindhu, B. (London Journal of Research in Humanities and Social Sciences, 2020)
Karate is a sport of skill and technique. It requires high fitness and is dependent on maximum levels of strength, speed, power, balance, and agility. Therefore, specific training is required to improve the performance to achieve success in this field. Aim: To identify various training methods for improvement in the sports performance of karate athletes in terms of physical and physiological variables. Methods: A literature search in Google Scholar, MEDLINE, and PubMed was conducted with many keywords. Studies conducted on male athletes or female athletes or both after the year 2005 to present and published in the English language were included in this review. The present study excluded the studies with abstract only and not open access. The present study was reported according to the Preferred Reporting Item for Systematic Reviews and Meta-analysis (PRISMA).